1981
DOI: 10.1104/pp.67.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Effects of Leaf Senescence on Membranes by Treatment with Paraquat

Abstract: Chloroplast and microsomal membranes from the primary leaf of bean acquired increasing proportions of gel phase lipid as the tissue senesced. The lipid-phase transition temperature for microsomes rose from about 25 to 43 C and that for chloroplasts rose from below -30 C to about 52 C within 5 weeks of planting. This was accompanied by large increases (2-to 4-fold) in the sterol to phospholipid ratio of the membranes, which reflected breakdown of phospholipid. Changes in fatty acid saturation were of insufficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…It was speculated that the change in their proportion is likely to be correlated with a change in physical properties of organellar membranes (Ben-Rais et al, 1993;Mishra et al, 1998). Besides, many studies have revealed that membranes in mature tissues are in liquid crystalline state, while in senescent tissue the membranes or a portion thereof, are in the crystalline gel phase at physiological temperatures (Lees and Thompson, 1980;Chia et al, 1981). Thus, the membrane phase alteration may be a consequence of qualitative changes in membrane lipids like glycolipids, phospholipids and MGDG/DGDG ratio.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was speculated that the change in their proportion is likely to be correlated with a change in physical properties of organellar membranes (Ben-Rais et al, 1993;Mishra et al, 1998). Besides, many studies have revealed that membranes in mature tissues are in liquid crystalline state, while in senescent tissue the membranes or a portion thereof, are in the crystalline gel phase at physiological temperatures (Lees and Thompson, 1980;Chia et al, 1981). Thus, the membrane phase alteration may be a consequence of qualitative changes in membrane lipids like glycolipids, phospholipids and MGDG/DGDG ratio.…”
Section: Resultsmentioning
confidence: 99%
“…nd = not detected. phospholipids ratio as senescence progresses (Chia et al, 1981;Mishra et al, 1998). In the present study, a 67-fold increase in the sterol/phospholipids ratio was observed for the Catharanthus leaf compared to that of the leaf at full maturity (Table 4).…”
Section: Lipid Profile During Growth and Senescence Of Catharanthus Rmentioning
confidence: 99%
“…Peroxidation of membrane lipids appears to be an inherent feature of senescence (7,8,16,22). The reactions of peroxidation can be initiated enzymically through lipoxygenase, and the finding that a proportion of the total lipoxygenase activity in senescing tissues is associated with membranes (16,17) suggests a role for this enzyme in the lipid peroxidation reactions of senescing membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Paraquat was used to simulate the ROS-induced damage caused by other environment stresses, such as drought, heat and salinity (Chia et al 1981, Bhatt et al 2011. The development of paraquat-resistant varieties could be an effective strategy to counteract various environmental stresses and ensure high crop yields.…”
Section: Introductionmentioning
confidence: 99%
“…• by up to ten-fold (Chia et al 1981). Paraquat was used to simulate the ROS-induced damage caused by other environment stresses, such as drought, heat and salinity (Chia et al 1981, Bhatt et al 2011.…”
Section: Introductionmentioning
confidence: 99%